Tindakan Perataan Laba Pada Perusahaan Jasa Di Indonesia Dengan Ukuran Perusahaan, Rasio Profitabilitas, Dan Leverage Sebagai Variabel Pembeda - Ainun Jariah (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2016)
The purpose of this research is to know that the measure of company, the ratio of profitability, and the leverage effect simultaneously and partially, also to know the dominant variables significantly to income smoothing action on the service companies listed on the Indonesia Stock Exchange. Based on calculations of index eckel, from the 42 companies there are 8 companies that don’t do the income smoothing, and 34 the rest do the income smoothing. Analysis tools used are analysis discriminant model z score. The results showed that simultaneous or partially 6 variables consist of the size of the company ( assets) , profit margin (PM ) , return on equity ( ROE ) , return on assets ( ROA ) , debt to equity ratio ( DER ) , and debt to total assets ( DTAR ) had no significant difference between companies do income smoothing and not income smoothing. Simultaneously the variables used to predict the income smoothing can influence to only 9.24 %. Base on a model of the cut - off point , the discriminant function able to predict the company it will do the income smoothing.